2014
DOI: 10.1007/s00423-014-1232-4
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous application of gentamicin collagen implants as prophylaxis of surgical site infections in laparoscopic colorectal surgery: a randomized, double-blinded, three-arm trial

Abstract: The local administration of GCS showed no significant benefit regarding wound infection after standardized laparoscopic colorectal resections. However, there was a trend toward reduced SSI in the GCS group. Therefore, a larger trial or meta-analysis is necessary to validate this result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Various studies have also used investigated the gentamicin-collage sponge in colorectal surgery [ 4 , 17 , 18 ]. A large-scale RCT [ 4 ] that involved all colorectal operations performed in 54 countries failed to prove the hypothesis that the gentamicin-collagen sponge would reduce the frequency of SSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have also used investigated the gentamicin-collage sponge in colorectal surgery [ 4 , 17 , 18 ]. A large-scale RCT [ 4 ] that involved all colorectal operations performed in 54 countries failed to prove the hypothesis that the gentamicin-collagen sponge would reduce the frequency of SSI.…”
Section: Discussionmentioning
confidence: 99%
“…A large-scale RCT [ 4 ] that involved all colorectal operations performed in 54 countries failed to prove the hypothesis that the gentamicin-collagen sponge would reduce the frequency of SSI. Similarly, an RCT [ 18 ] that included 291 patients who underwent laparoscopic colorectal surgery at a single center also failed to prove the efficacy of the gentamicin-collagen sponge. However, in a recent meta-analysis [ 5 ], a sensitivity analysis of abdominal wounds revealed that a gentamicin-collagen sponge could reduce SSI in colorectal surgery (RR, 0.38; 95% CI, 0.20–0.72).…”
Section: Discussionmentioning
confidence: 99%
“…1,[11][12][13][14][15] Many researchers have demonstrated that the application of gentamicin sponges can significantly reduce the incidence of wound infection and kill pathogenic bacteria in both animal experiments and clinical studies. 5,16,17 However, there are also many scholars who believe that gentamicin sponges have no effect in the prevention or treatment of wound infections and that these sponges may in fact have the opposite effect and increase the incidence of infection. 1,7,8,18,19 In particular, a study with a large sample size was previously conducted to confirm these opinions.…”
Section: Discussionmentioning
confidence: 99%
“…Gentamicin-sponge has been studied for more than 30 years, but its e cacy is still controversial [1,[11][12][13][14][15]. Many researches have demonstrated that the application of gentamicin-sponge can signi cantly reduce the incidence of wound infections and kill pathogenic bacteria, whether in animal experiments or clinical studies [5,[16][17]. However, also many scholars believe that gentamicin-sponge has no effect on preventing or treating wound infection, and it maybe play an opposite role as increase the incidence of infection [1,[7][8][18][19].…”
Section: Discussionmentioning
confidence: 99%